CGMP manipulation in cardiometabolic disease: chances and challenges. (July 2019) - Jordan, Jens; Hildebrand, Staffan; Pfeifer, Alexander
Abstract : Purpose of review: Cardiovascular and metabolic diseases are closely linked and commonly occur in the same patients. This review focuses on the cyclic guanosine monophosphate (cGMP) system and its crosstalk between metabolism and the cardiovascular system. Recent findings: Recent studies suggest that cGMP, which serves as second messenger for nitric oxide and for natriuretic peptides, improves oxidative metabolism and insulin signaling. The clinical evidence is particularly strong for the natriuretic peptide branch of the cGMP system. Clinical trials suggested improvements in insulin sensitivity and reductions in the risk of progressing to type 2 diabetes mellitus. However, further studies are needed. Summary: Enhancing cGMP signaling through nonpharmacological or pharmacological means may improve glucose metabolism in addition to affecting the cardiovascular system. However, excessive cGMP production could have significant unwanted cardiovascular and metabolic effects.